Supplemental 18F-FDG-PET/CT for detection of malignant transformation of IPMN: a model-based cost-effectiveness analysis - Bicu, Felix; Rink, Johann; Froelich, Matthias F.; Cyran, Clemens Christian Joachim; Rübenthaler, Johannes; Birgin, Emrullah; Röhrich, Manuel; Tollens, Fabian (Cancers, 2021)
Accurate detection of malignant transformation and risk-stratification of intraductal papillary mucinous neoplasms (IPMN) has remained a diagnostic challenge. Preliminary findings have indicated a promising role of positron emission tomography combined with computed tomography and 18F-fluorodeoxyglucose (18F-FDG-PET/CT) in detecting malignant IPMN. Therefore, the aim of this model-based economic evaluation was to analyze whether supplemental FDG-PET/CT could be cost-effective in patients with IPMN. Decision analysis and Markov modeling were applied to simulate patients’ health states across a time frame of 15 years. CT/MRI based imaging was compared to a strategy with supplemental 18F-FDG-PET/CT. Cumulative costs in US-$ and outcomes in quality-adjusted life years (QALY) were computed based on input parameters extracted from recent literature. The stability of the model was evaluated by deterministic sensitivity analyses. In the base-case scenario, the CT/MRI-strategy resulted in cumulative discounted costs of USD $106,424 and 8.37 QALYs, while the strategy with supplemental FDG-PET/CT resulted in costs of USD $104,842 and a cumulative effectiveness of 8.48 QALYs and hence was cost-saving. A minimum specificity of FDG-PET/CT of 71.5% was required for the model to yield superior net monetary benefits compared to CT/MRI. This model-based economic evaluation indicates that supplemental 18F-FDG-PET/CT could have a favorable economic value in the management of IPMN and could be cost-saving in the chosen setting. Prospective studies with standardized protocols for FDG-PET/CT could help to better determine the value of FDG-PET/CT.
Im Titel ist "18" hochgestellt
Gesehen am 31.05.2021